Respostas

2014-02-13T19:09:08-02:00
(x+3)2 = 2x (x-5)                                                                                                          x2 + 9 = 2x2 - 10x + 9                                                                                                x2 - 2x2 + 10x = 9-9
x2 + 10x = 0
11x2 = 0
x2= 11
x = 11  dividido por 2 
x = 5,5
A melhor resposta!
2014-02-13T19:10:10-02:00
(x+3)^2 = 2x (x-5) + 9
x^2 + 3^2 = 2x^2 - 10x + 9
0 = 2x^2 -10x + 9 -x^2 - 3^2
0 = x^2 - 10x + 9 - 9 
0 = x^2 - 10x

Δ = b^2 - 4ac
Δ = (-10)^2 - 4(1)(0)
Δ = 100

x = -b ± √Δ/2a
x = -(-10) ± √100 / 2(1)
x = 10 ± 10 / 2

x' = 10 + 10 / 
2 = 10
x'' = 10 - 10 / 2  = 0

Espero ter ajudado :D

1 5 1